1997
DOI: 10.1002/pro.5560060813
|View full text |Cite
|
Sign up to set email alerts
|

The effect of denaturants on protein structure

Abstract: Virtually all studies of the protein-folding reaction add either heat, acid, or a chemical denaturant to an aqueous protein solution in order to perturb the protein structure. When chemical denaturants are used, very high concentrations are usually necessary to observe any change in protein structure. In a solution with such high denaturant concentrations, both the structure of the protein and the structure of the solvent around the protein can be altered. X-ray crystallography is the obvious experimental tech… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
92
1

Year Published

1998
1998
2014
2014

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 108 publications
(96 citation statements)
references
References 48 publications
3
92
1
Order By: Relevance
“…5B). Low concentrations of guanidine hydrochloride enhance the fluorescence of the domain (Ϯ metal ions), suggesting a possible interaction between GdnHCl and the DNase that has been documented for other proteins (35). The fluorescence of the fully denatured protein was the same regardless of its metal loading, indicating that the fluorescence of the unfolded states of the apo-and holoenzyme are the same.…”
Section: Conformational Stability Changes Of the E9 Dnase Domain On Bmentioning
confidence: 68%
“…5B). Low concentrations of guanidine hydrochloride enhance the fluorescence of the domain (Ϯ metal ions), suggesting a possible interaction between GdnHCl and the DNase that has been documented for other proteins (35). The fluorescence of the fully denatured protein was the same regardless of its metal loading, indicating that the fluorescence of the unfolded states of the apo-and holoenzyme are the same.…”
Section: Conformational Stability Changes Of the E9 Dnase Domain On Bmentioning
confidence: 68%
“…The change in heat capacity of unfolding measured with heat unfolding and denaturant-induced unfolding are different, indicating that chemical denaturant may participate directly in the process (41). Discrete denaturant binding sites and low B-factors of surface residues have also been observed in the X-ray crystal structures of proteins in the presence of GdmCl (7,8,42).…”
Section: Discussionmentioning
confidence: 99%
“…D enaturants such as guanidinium chloride (GdmCl) and urea are classic perturbants used to probe the thermodynamics and kinetics of protein conformational changes, although their mechanism of action is poorly understood (1)(2)(3)(4)(5)(6)(7)(8)(9)(10)(11)(12)(13)(14)(15). In some of these studies, a dry molten globular (DMG) state has been observed on the native side of the free-energy barrier (16)(17)(18).…”
mentioning
confidence: 99%
“…55,56 In the case of cyt c, Thomas et al 48 proposed that a guanidinium ion may displace the side-chain of Arg38 in cyt c, which forms a functionally important salt bridge involving the buried heme propionate side-chain. 57 To address this possibility, we carried out a detailed comparison of the GuHCl and urea-induced unfolding transitions for H33N cyt c. In the absence of specific binding effects, we expect that the free energy of unfolding extrapolated to cZ0 is independent of the denaturant used.…”
Section: Discussionmentioning
confidence: 99%